Antibodies to Factor XII Are Distinct from Antibodies to Prothrombin in Patients with the Anti-phospholipid Syndrome - Jones, D. W.; Nicholls, P. J.; Donohoe, S.; Gallimore, M. J.; Winter, M. (Thrombosis and Haemostasis, 2002)
Patients with the anti-phospholipid syndrome (APS) have antiphospholipid antibodies (aPA) which are often targeted towards phospholipid binding proteins such as β2-glycoprotein I and prothrombin. Antibodies to factor XII (FXIIabs) have also been identified in some patients with APS. Factor XII (FXII) is a member of the kringle family of proteins which include plasminogen and prothrombin. Antibodies to prothrombin have been associated with myocardial infarction and have been shown to cross react with plasminogen.Sixteen patients with APS and FXIIabs were investigated for the presence of antibodies to prothrombin, by enzyme linked immunosorbent assay in a calcium (Ca++) independent assay. All sixteen showed different antibody binding patterns than those observed for antibodies to FXII.Eight patients were further investigated using surface plasmon resonance (SPR) for antibody binding to covalently bound FXII and to covalently bound prothrombin in both Ca++ dependent and independent systems. Of three patients demonstrating antibody binding to FXII by SPR, none demonstrated antibody binding to prothrombin in a Ca++ independent system with one demonstrating antibody binding to prothrombin that was Ca++ dependent. Of five patients who did not bind FXII by SPR, one demonstrated antibody binding to prothrombin in a Ca++ independent system while two demonstrated antibody binding to prothrombin in a Ca++ dependent system. Antibodies to FXII in patients with APS appear to be distinct from antibodies to prothrombin.
Keywords: Factor XII; anti-phospholipid syndrome; prothrombin; antibodies to factor XII